1978
DOI: 10.4039/ent110475-5
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF THE RE-EMERGENCE PROCESS OF PARENT ADULT DENDROCTONUS FRONTALIS (COLEOPTERA: SCOLYTIDAE)

Abstract: Can. Ent. 110: 471-473 (1978) Xenoborus Reuter is synonymized with Tropidosteptes Uhler. Tropidostepres brooksi n. sp. is described from Saskatchewan, Manitoba, Ontario, and Quebec. The species was collected on Fraxinus spp. Reuter (1908) described Neoborus commissuralis and proposed the subgenus Xenoborus for it. Soon after (1909) he transferred commissuralis to Tropidosteptes Uhler (1 878) and described petitti and plagifer under that genus. Van Duzee (1 9 16a, b ) raised Xenoborus to generic status and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
2

Year Published

1980
1980
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 8 publications
2
20
0
2
Order By: Relevance
“…Each successfully emerged brood adult is capable of colonizing and producing offspring in more than one host tree (Cooper and Stephen 1978;Coulson et al 1978). Once successfully attacked, the infested tree will die.…”
Section: Impact Of Mortality Caused By Natural Enemiesmentioning
confidence: 99%
“…Each successfully emerged brood adult is capable of colonizing and producing offspring in more than one host tree (Cooper and Stephen 1978;Coulson et al 1978). Once successfully attacked, the infested tree will die.…”
Section: Impact Of Mortality Caused By Natural Enemiesmentioning
confidence: 99%
“…Particularly, the long‐distance migration is evidenced by Borden () and Hedden and Billings (). It is found that the SPB population density follows spatiotemporal patterns during each stage of SPB life history, that is, colonization (Fargo et al., ), reemergence (Coulson et al., ), survivorship (Coulson et al., ), and emergence (Coulson, Pulley, Foltz, Martin, & Kelley, ). In addition, research on broadscale SPB risks also found spatiotemporal patterns of probabilities of SPB outbreaks (e.g., Gumpertz, Wu, and Pye, ; Pye et al., ; Zhu et al., ).…”
Section: Empirical Analysismentioning
confidence: 99%
“…With realistic parameter sets, the number of hosts attacked has the greatest effect on generational overlap by setting the upper limit on adult lifespan. Field observations suggest that attacks by re-emerged adults are integral to sustaining infestation growth (Coulson et al 1978;Coulson 1980), but Thatcher & Pickard (1964) noted that SPB do not produce more than two broods in nature. We allowed model adults to lay a maximum of two sequential broods and manipulated the probability of re-emergence and betweenhost survival to test the effect of adult mortality on population continuity.…”
Section: Effect Of Adult Mortalitymentioning
confidence: 99%